Towards sustainable CO2 electrochemical transformation via coupling design strategy. (November 2022) - Song, Xinning; Jia, Shunhan; Xu, Liang; Feng, Jiaqi; He, Lei; Sun, Xiaofu; Han, Buxing
Abstract: CO2 is a notorious greenhouse gas, but it is also an abundant, non-toxic, and sustainable C1 source. CO2 electrochemical transformation (CO2 ET) is an effective way to close the artificial carbon cycle. Coupling design strategies guided by green chemistry are widely utilized in CO2 ET because they can effectively optimize chemical performance, economic feasibility, and sustainability. The current review presents recent advances of coupling strategies in a progressively macroscopic view: from co-electrodes, counter electrodes to carbon capture, utilization and storage (CCUS) processes. Specifically, this review summarizes the coupling design in the electro-organic conversion of CO2, including co-electrolysis with organic and inorganic substrates at the cathode. We also discuss the coupling of CO2 ET with paired anodic oxidation reactions. Literarily available anodic substrates contain chlorine compounds, biomass derivatives, alcohols, and amines. In addition, existing applications of coupling strategies in CO2 ET processes are summarized, including coupling with capture-media, multi-physical fields, and product utilization. Finally, the challenges encountered in the coupling design strategy are presented, and future developments are envisioned. Graphical abstract: Image 1 Highlights: CO2 electrochemical transformation is an effective way to close the artificial carbon cycle. The coupling design strategy is an attractive strategy to efficiently convert CO2 with improved chemical performance and enhanced energy utilization efficiency. This paper reviews the application of coupling design strategies in the electro-conversion of CO2, including coupling with the cathode, coupling with the anode, and multi-physical field coupling. Providing some perspectives on the challenge for future research in CO2 electrochemical transformation.